DEVELOPMENT OF PROFESSIONAL SKILLS IN FEMALE STUDENTS STUDENTS IN VOLLEYBALL EDUCATION - Alyona Andreyevna Tunyan (Bright Mind Publishing, 2025)
This article analyzes the theoretical and methodological aspects of the formation of professional skills in female students studying volleyball. The main focus is on the replacement of practical training and theoretical knowledge in the formation of professional skills of students specializing in volleyball coaching. The main elements and methods of the educational process aimed at the development of professional competences are considered in the article.
Keywords: Volleyball, professional skills, female students, theoretical and methodological aspects, training.